Perkembangan Struktur Ruang di Kota Makassar - Aryanto Aryanto; Slamet Trisutomo; Zenaide Toban (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
The spatial structure is a manifestation of the utilization of urban space. In the development of a city, spatial structure become one of the elements that can be viewed in determining the direction, shape, and the change of these developments. Makassar City is a city with views of growth history of this period the city of Makassar starting from the kingdom of Gowa-Tallo period until now, Makassar city has far developed into one of the modern city. Therefore, we can see how the spatial structure formed in the period of kingdom until now or may be called the period of reformation. This research was conducted with a literature review as the basis for the preparation of research reports that can identify the spatial structure developments in Makassar City based on above period and knowing the factors that influence these developments. This study found out the history of the development of Makassar City, spatial sructure theory, and urban morphology. This research aims to identify the spatial structure in Makassar City started from pra-colonial period until the reformation period. The research variable component consists of studies on the urban spatial structure base on theory such as the location of central business development (CBD), space utilization and urban morphology such as land use and street pattern. Then these variables were analyzed descriptively by looking at the development of Makassar City started from the pra-colonial or kingdom period until reformation period. Analysis method used in this case concerned a history analysis and photo mapping analysis to show mapping of these variable component. Then, the factors that influence the development of spatial structure in Makassar City, the variable component refers to the variable component of the development of their own spatial structure with using the same analysis tools.